The effect of probiotic supplementation on blood pressure, systemic inflammation and endothelial function in patients with arterial hypertension - Tovstyha, Vladyslav; Shypulin, Vadym (The Ukrainian Scientific Medical Youth Journal, 2025)
The need for new therapeutic approaches to the treatment of arterial hypertension is due to its increasing prevalence and high mortality rate, which prompts the search for new methods of therapy. Recent scientific data indicate the important role of gut microbiome imbalance, which can lead to disruption of the gut barrier and the development of chronic low-intensity systemic inflammation. This inflammation is a key mechanism in the pathogenesis of arterial hypertension and causes endothelial dysfunction, as evidenced by higher levels of pro-inflammatory cytokines. This highlights new therapeutic perspectives for the correction of gut dysbiosis as a therapeutic strategy with the potential to improve disease control. The aim of this prospective study was to evaluate the effect of dietary probiotic supplementation on blood pressure, systemic inflammation and endothelial function in patients with arterial hypertension through correction of gut dysbiosis. The study involved fifty-five patients who were randomized into two groups: the main group (30 people), which, in addition to standard antihypertensive therapy, received a probiotic that included Saccharomyces boulardii and Lactobacillus, and a comparison group (25 people) receiving only standard therapy. The duration of observation was 3 months. All participants underwent a comprehensive clinical examination with analysis of systolic and diastolic blood pressure, levels of interleukin-6 and interleukin-10, assessment of endothelium-dependent vasodilation of the brachial artery, as well as analysis of the composition of the gut microbiome. The study found that before the intervention, the groups were comparable in terms of basic clinical and demographic indicators, with the exception of a significant difference in the proportion of patients with reduced Roseburia content inulinivorans and Faecalibacterium prausnitzii, which limited the direct comparison of the dynamics of these taxa. After 3 months of observation, patients in the main group achieved a significant decrease in systolic and diastolic blood pressure, as well as the level of pro-inflammatory cytokine interleukin-6, while in the comparison group the levels of inflammatory markers did not change significantly. Microbiome analysis showed that the probiotic supplementation effectively corrected gut dysbiosis, as evidenced by a significant decrease in the ratio of Firmicutes to Bacteroidetes, a decrease in the proportion of Firmicutes, and an increase in the proportion of Bacteroidetes and Lactobacillus. At the same time, comparative analysis did not reveal a statistically significant difference in endothelial function indicators between the groups. The results obtained confirm that dietary probiotic supplementation is an effective adjunct method for correcting gut dysbiosis, which helps improve blood pressure control and reduce systemic inflammation in patients with arterial hypertension, which is important for improving the prognosis of the disease.